2017
DOI: 10.1287/mnsc.2016.2479
|View full text |Cite
|
Sign up to set email alerts
|

Channel Integration, Sales Dispersion, and Inventory Management

Abstract: We study the effects of the introduction of cross-channel functionalities on the overall sales dispersion of retailers and the implications of these effects for inventory management. To do that, we analyze data from a leading U.S. retailer who introduced a “ship-to-store” (STS) functionality that allows customers to ship products to their local store free of charge when those products are not available in their local store. Based on the fact that stores prioritize carrying products for which local demand is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(64 citation statements)
references
References 42 publications
3
59
0
2
Order By: Relevance
“…From the retail standpoint, some authors have conducted in-depth research into the integration between physical and virtual channels, confirming the generation of competitive advantage as a result of integration [28]. Likewise, according to [29], channel integration is a key factor for inventory management, while the quality of channel integration positively influences perceived fluency [30].…”
Section: Omni-channel Retailingmentioning
confidence: 93%
“…From the retail standpoint, some authors have conducted in-depth research into the integration between physical and virtual channels, confirming the generation of competitive advantage as a result of integration [28]. Likewise, according to [29], channel integration is a key factor for inventory management, while the quality of channel integration positively influences perceived fluency [30].…”
Section: Omni-channel Retailingmentioning
confidence: 93%
“…The inventory turnover ratio measures the number of times inventory has been sold and replaced during the year. It is a good measure whether the inventory is obsolete if there are efficient buying practices and inventory management in general (Hançerlioğulları, Şen, & Ağca Aktunç, 2016;Ballou, 2000;Biggart & Gargeya, 2002;Gallino, Moreno, & Stamatopoulos, 2016;Balcik, Bozkir, & Kundakcioglu, 2016). Where low ratio suggests weaker sales and potentially surplus inventory where high ratio suggests stronger sales in total high ratio can suggest insufficient inventory levels (Hançerlioğulları et al, 2016;Ballou, 2000;Biggart & Gargeya, 2002;Bromiley et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is potential for researchers in these methodological communities to inform each other's research. Our analysis of the extant Trends are also beginning to be identified empirically; Gallino et al (2016) identified greater sales dispersion when a retailer adds STS to its omnichannel capabilities. In addition, Kull et al (2013) demonstrated how channel fulfillment within an omnichannel DC can lead to different types of inventory inaccuracy.…”
Section: An Agenda For Future Inquirymentioning
confidence: 97%
“…For example, buy-in-store-deliver-to-store is fulfilled identically as an STS order. Buy-in-storedeliver-to-home is fulfilled the same as an online order (Agatz et al, 2008;Gallino et al, 2016).…”
Section: Purchase Originationmentioning
confidence: 99%
See 1 more Smart Citation